Parallel P-PD controller to achieve vibration and position control of a flexible beam - Abbas, Ammar N.; Irshad, Muhammad Asad (IAES International Journal of Robotics and Automation (IJRA), 2021)
Robotic arms are considered as a cantilever beam fixed at one end and due to the length-to-weight ratio, it has a significant vibration-induced that needs to be controlled to achieve accurate position, speed control and to increase its efficiency. In this project, a discretized Timoshenko beam model is used to discuss the dynamics of the system. Further, to implement the control on the hardware an experimental setup is fabricated to observe the open-loop and closed-loop responses of the beam made of low-density polyethylene. An accelerometer as a feedback sensor is attached at one end of the flexible beam while another end is fixed at the moving cart having DC motor as an actuator. Simulink is used as the programming tool to perform all of the experimentation. Proportional-integral-derivative (PID) tuning is performed. Following that open-loop responses of the deflection of the beam parallel to the motion are observed with different input waveforms. By applying a proportional control scheme, another experiment is performed to demonstrate the disturbance rejection with an accelerometer as a feedback sensor, while ignoring position control. Finally, a PD and P based parallel control scheme is proposed to obtain simultaneously both position control and vibration reduction.